2016
DOI: 10.1128/mbio.01114-16
|View full text |Cite
|
Sign up to set email alerts
|

A Full-Length Infectious cDNA Clone of Zika Virus from the 2015 Epidemic in Brazil as a Genetic Platform for Studies of Virus-Host Interactions and Vaccine Development

Abstract: An arthropod-borne virus, Zika virus (ZIKV), has recently emerged as a major human pathogen. Associated with complications during perinatal development and Guillain-Barré syndrome in adults, ZIKV raises new challenges for understanding the molecular determinants of flavivirus pathogenesis. This underscores the necessity for the development of a reverse genetic system based on an epidemic ZIKV strain. Here, we describe the generation and characterization in cell cultures of an infectious cDNA clone of ZIKV isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
158
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 43 publications
4
158
1
Order By: Relevance
“…Toward that end, several reverse genetics systems have been developed to support these critical research needs. Interestingly, virus rescued from these systems has been found to be fairly significantly attenuated in cell cultures, mice, and other systems (16,17). Although the reasons for this rather severe attenuation are not fully clear at present, an important characteristic of infectious clones is the degree to which they mimic critical phenotypes of wild-type uncloned virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward that end, several reverse genetics systems have been developed to support these critical research needs. Interestingly, virus rescued from these systems has been found to be fairly significantly attenuated in cell cultures, mice, and other systems (16,17). Although the reasons for this rather severe attenuation are not fully clear at present, an important characteristic of infectious clones is the degree to which they mimic critical phenotypes of wild-type uncloned virus.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models for ZIKV neuropathogenesis and in utero transmission have recently been reported in mice deficient in innate immune responses by using African and Asian genotype isolates (12)(13)(14)(15), though there have not been in vivo pathogenesis studies using an isolate from the American outbreak. In addition, infectious clones for Asian genotype ZIKV strains have recently been described, including one from a virus circulating in the American outbreak (16,17). These clones, however, are attenuated in vitro and in vivo, somewhat limiting their utility for certain types of studies.…”
mentioning
confidence: 99%
“…We set out to examine if N-linked glycosylation within the VNDT motif plays any role in ZIKV pathogenicity in an immunocompromised-mouse model. Although infectious clones of MR766 viruses (25,28,29), as well as several other ZIKV isolates (26,27,47), have been reported, the role of VNDT or glycosylation in this region in pathogenicity has not been explored. A recent study using ectopic expression and pseudoparticle formation with a WNV replicon showed that N-glycosylation of ZIKV E protein is necessary for efficient particle assembly and infectivity (48).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study has shown that a single amino acid substitution (A188V) in the viral NS1 protein is critical for NS1 antigenemia, which in turn facilitates ZIKV acquisition by mosquitoes from viremic animals (24). With the availability of infectious clones of ZIKV (25)(26)(27)(28)(29)47) from historical and contemporary isolates, it will be possible to further examine the specific changes in the viral genome that are responsible for viral transmission, replication, virulence, and tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation